Stimulation of cell adhesion at nanostructured teflon interfaces - Kruss, Sebastian; Wolfram, Tobias; Martin, Raquel; Neubauer, Stefanie; Kessler, Horst; Spatz, Joachim P. (Advanced materials, 2010)
Tunable gold nanoparticle patterns have been immobilized onto amorphous teflon surfaces in a stable manner. This method provides a general route to covalently link biomolecules onto chemically inert teflon surfaces, which enhances endothelialization.
Gesehen am 06.03.2023